Progress in the Application of Organoids-On-A-Chip in Diseases - Qiao Geng; Yanyan Xu; Yang Hu; Lu Wang; Yi Wang; Zhimin Fan; Desong Kong (Organogenesis)
With the rapid development of the field of life sciences, traditional 2D cell culture and animal models have long been unable to meet the urgent needs of modern biomedical research and new drug development. Establishing a new generation of experimental models and research models is of great significance for deeply understanding human health and disease processes, and developing effective treatment measures. As is well known, long research and development cycles, high risks, and high costs are the “three mountains” facing the development of new drugs today. Organoids and organ-on-chips technology can highly simulate and reproduce the human physiological environment and complex reactions in vitro, greatly improving the accuracy of drug clinical efficacy prediction, reducing drug development costs, and avoiding the defects of drug testing animal models. Therefore, organ-on-chips have enormous potential in medical diagnosis and treatment.